Biliary Epithelial Senescence in Liver Disease: There Will Be SASP - Meadows, Vik; Baiocchi, Leonardo; Kundu, Debjyoti; Sato, Keisaku; Fuentes, Yessenia; Wu, Chaodong; Chakraborty, Sanjukta; Glaser, Shannon; Alpini, Gianfranco; Kennedy, Lindsey; Francis, Heather (Frontiers in Molecular Biosciences, 2021)
Cellular senescence is a pathophysiological phenomenon in which proliferative cells enter cell cycle arrest following DNA damage and other stress signals [1; 2]. Telomeres are protective terminal sequences of chromosomes that dampen the natural, permanent DNA damage that occurs after repetitive cell division; however, acute stress can amplify double-stranded DNA damage and push cells into premature senescence [3]. In recent years, there has been increased evidence for the role of premature senescence in disease progression including diabetes, cardiac diseases, and end-stage liver diseases [4; 5; 6]. Liver size and function change with aging, and presumably with increasing cellular senescence, so it is important to understand the mechanisms by which cellular senescence affects the regenerative nature of the liver in health and disease [7].